Hubungan Antara Asupan Magnesium, Asupan Lemak Dan Status Gizi Dengan Tekanan Darah Pada Wanita Menopause Hipertensi Di RSUD Sukoharjo - Lestari, Puji; , Elida Soviana, S.Gz.,M; , Rusdjianto, SKM.,Msi (2016)
The risk of hypertension in women increases after experiencing menopause due to a decrease in estrogen and progesterone hormones results in a decrease in endothelial cells the elasticity function that can affect blood pressure. The prevalence of hypertension in Sukoharjo general hospital as much as 9.4% and increased by 84% over the last 3 years between the years 2012-2014. To determine the relationship of magnesium intake, fat intake and nutritional status to the blood pressure among hypertensive menopausal women at Sukoharjo general hospital. This research is observational study with cross sectional design. Total subjects of 30 menopausal hypertensive were selected through systemic consequtive sampling. Magnesium intake and fat intake obtained through semiquantitative food frequency. The nutritional status obtained by BMI (Body Mass Index) while the blood pressure was obtained from hospital medical records. 73.3% of the subjects has enough magnesium intake while 76.7% of the subject has high fat intakes. A total of 60% of the subjects were overnutrition, and 70% of the subjects had hypertension type II. The results show that magnesium intake is associated with systolic blood pressure (p= 0,001) and diastolic blood pressure (p= 0,002). Fat intake has a relationship with systolic and diastolic blood pressure with p= 0,025 andp= 0,02 respectively. Nutritional status also has a relationship with systolic and diastolic blood pressure with p= 0.004 and p= 0,006 respectively. There is a relationship of blood pressure to magnesium intake, fat intake and nutritional status.